(untitled) (American Journal of Islam and Society, 2022)
Seeking knowledge from scholars is an imperative for Salafis. But what does that mean for Salafis in the West who deny that there are any scholars among them? Since the 1960s, Western Muslims have been taking advantage of the scholarships available for Islamic studies programs in Saudi Arabia. A steady stream of students has gone, studied with leading Salafi scholars in the heart of the Muslim world, and returned home to promulgate Salafi teachings and lead their communities. Why do none of these former students count as scholars? If they are not scholars, then what is the nature of their role as local leaders? To answer these questions, this study looks closely at the predominantly African American Salafi affiliate community in Philadelphia. The arguments here contribute to a growing body of literature on global Salafism and specifically studies of so-called Madkhalī communities tied to the Islamic University of Medina. Primary fieldwork from 2010 to 2013 and interviews as recent as 2021 inform the conclusion that this community’s pattern of knowledge transmission perpetuates and even celebrates the continual reliance of Philadelphia’s Salafis on scholars abroad.